Impact of a short exposure to levofloxacin on faecal densities and relative abundance of total and quinolone-resistant Enterobacteriaceae. (July 2016) - Bernard, J.; Armand-Lefèvre, L.; Luce, E.; El Mniai, A.; Chau, F.; Casalino, E.; Andremont, A.; Ruppé, E.
Abstract: Emergence of resistant Enterobacteriaceae in the intestinal microbiota during antibiotic treatment is well documented but its early dynamic is not. Here, we compared the densities of total Enterobacteriaceae and relative abundance (RA) of quinolone-resistant Enterobacteriaceae (QRE) in the first stool passed by patients who had a short exposure to levofloxacin (levofloxacin, n  = 12) or not (control, n  = 8). Mean densities (SD) (log CFU/g stool) of total Enterobacteriaceae were lower in the levofloxacin group than in the control group—3.4 (1.6) versus 6.7 (1.7), respectively, p <0.001. Conversely, mean RA (SD) of QRE was significantly higher in the levofloxacin group than in the control group—49.7% (23.4) versus 0.1% (3.2), respectively, p <0.05). In conclusion, even a short exposure to levofloxacin has a profound impact on the densities of total Enterobacteriaceae and the QRE-RA.